2016
DOI: 10.3389/fnhum.2016.00646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensity of Facial Expressions on Amygdalar Activation Independently of Valence

Abstract: For several stimulus categories (e.g., pictures, odors, and words), the arousal of both negative and positive stimuli has been shown to modulate amygdalar activation. In contrast, previous studies did not observe similar amygdalar effects in response to negative and positive facial expressions with varying intensity of facial expressions. Reasons for this discrepancy may be related to analytical strategies, experimental design and stimuli. Therefore, the present study aimed at re-investigating whether the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
(135 reference statements)
2
11
0
Order By: Relevance
“…In addition, the posterior STS and supramarginal gyrus have been reported to be involved in the integration of audio-visual information and to respond to multiple types of social signals 74,75 . The results of the present study extend the findings of Lin and colleagues 5 and indicate arousal-driven modulation of the posterior STS by facial and vocal expressions.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the posterior STS and supramarginal gyrus have been reported to be involved in the integration of audio-visual information and to respond to multiple types of social signals 74,75 . The results of the present study extend the findings of Lin and colleagues 5 and indicate arousal-driven modulation of the posterior STS by facial and vocal expressions.…”
Section: Discussionsupporting
confidence: 91%
“…In line with these studies, we find a significant positive relationship between amygdalar activation and stimulus arousal, and thus also a positive relationship between amygdalar activation and emotional intensity of facial expressions. Regarding facial expressions, several other studies found effects of emotional intensity on amygdalar responding 5,29,35 , which however varied. Interestingly, Gerber and colleagues 35 observed inverse intensity effects, that is, enhanced amygdalar responding www.nature.com/scientificreports www.nature.com/scientificreports/ for weak, possibly ambiguous expressions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations